Fracture network, fluid pathways and paleostress at the Tolhuaca geothermal field. (March 2017) - Pérez-Flores, Pamela; Veloso, Eugenio; Cembrano, José; Sánchez-Alfaro, Pablo; Lizama, Martín; Arancibia, Gloria
Abstract: In this study, we examine the fracture network of the Tolhuaca geothermal system located in the Southern Andean volcanic zone that may have acted as a pathway for migration and ascent of deep-seated fluids under the far/local stress field conditions of the area. We collected the orientation, slip-data and mineralogical content of faults and veins recovered on a ca. 1000 m deep borehole (Tol-1) located in the NW-flank of the Tolhuaca volcano. Tol-1 is a non-oriented, vertical borehole that recovered relatively young (<1 Ma) basaltic/andesitic volcanic rocks with subordinate pyroclastic/volcanoclastic interbedded units of Pleistocene age. Here, we examined and measured the inclination, geometry, texture, mineralogy, and relative sense of displacement of veins and faults. To determine the actual azimuthal orientation of fault and veins we reoriented 66 segments (89 standard mini-cores) of Tol-1 using stable Characteristic remanent magnetization component (ChRM) obtained by thermal demagnetization methodology. Paleo-declination of ChRM vectors was used to re-orient the borehole pieces, as well as fault and veins, to a common anchor orientation value consistent with the Geocentric Axial Dipole approximation (GAD). Inversion of RM-corrected fault-slip data reveals a local tensional stress field with a vertically oriented σ1 axis (083/74) and a subhorizontal, NS-trending σ3 axis (184/03). Within the topmost 400 m of the borehole, faults and veins are randomly oriented, whereas below 400 m depth, faults and veins show preferential NE-to EW-strikes and steep (>50°) dips. The EW-striking veins are compatible with the calculated local stress field whereas NE-striking veins are compatible with the regional stress field, the morphological elongation of volcanic centers, alignments of flank vents and dikes orientation. Our results demonstrate that the paleomagnetic methodology proved to be reliable and it is useful to re-orient vertical boreholes such as Tol-1. Furthermore, our data show that the bulk transpressional regional stress field has local variations to a tensional stress field within the NE-striking fault zone belonging to the Liquiñe-Ofqui Fault System, favoring the activation of both NW- and NE-striking pre-existent discontinuities, especially the latter which are favorably oriented to open under the prevailing stress field. The vertical σ1 and NS-trending subhorizontal σ3 calculated in the TGS promote the activation of EW-striking extensional veins and both NE and NW-striking hybrid faults, constituting a complex fluid pathway geometry of at least one kilometer depth. Graphical abstract: Highlights: We mapped a non-oriented drill core from Tolhuaca Geothermal System (TGS) in the Andes. Paleomagnetic re-orientation of the core yielded the actual geographic orientation of faults and veins. Fault-slip data provided a local tensional stress field at the TGS. The calculated stress field is kinematically compatible with the identified hydrothermal fluid pathways.